SISTEM INFORMASI AKSES PELAYANAN MARKAS ( YANMA ) MENGGUNAKAN PHP DAN MYSQL DI POLDA BENGKULU - Siswanto, Siswanto; Suwarni, Suwarni (Jurnal Media Infotama, 2011)
This study aims to make information systems at Headquarters Services unit (YANMA) Bengkulu Police with the PHP programming language and information MySQL.Sistem Headquarters Services (YANMA) is one form of simplification of the system of documentation of data and service activities as well as the headquarters can be a medium of information for the public about the functions, tasks and activities carried out by the Service Headquarters (YANMA) in Bengkulu Provincial Police. Headquarters Services information systems (YANMA) can be accessed through Bengkulu Police http://yanma.baseba.com address. The information displayed among other profiles, vision and mission, organizational structure, personnel information, the task of setting information, information activities, galleries, tools and supplies and guest book.